2020
DOI: 10.1155/2020/8723062
|View full text |Cite|
|
Sign up to set email alerts
|

Government Intervention, Financial Support, and Comprehensive Efficiency of Enterprise Independent Innovation: Empirical Analysis Based on the Data of Chinese Strategic Emerging Industries

Abstract: Government intervention and financial support are two major means to promote the independent innovation performance of enterprises in strategic emerging industries, and government intervention has induced crowding-out effects on financial support, which leads to the uncertainty of the dual incentive effect of government intervention and financial support on enterprises’ independent innovation. The research object of this paper is 657 strategic emerging enterprises listed in Shanghai and Shenzhen. We empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The results showed that R&D internationalization helps to improve the innovation efficiency of electronics manufacturing firms (Zhong et al, 2021). The influencing factors of enterprises' independent innovation performance was explored, and the results showed that the comprehensive efficiency of independent innovation is increasing (Zhou et al, 2020).…”
Section: Research On Technology Innovationmentioning
confidence: 99%
“…The results showed that R&D internationalization helps to improve the innovation efficiency of electronics manufacturing firms (Zhong et al, 2021). The influencing factors of enterprises' independent innovation performance was explored, and the results showed that the comprehensive efficiency of independent innovation is increasing (Zhou et al, 2020).…”
Section: Research On Technology Innovationmentioning
confidence: 99%
“…In addition to the type of regional innovation, it can be shown the results of the identification of the form of regional innovation that distinguished three forms of innovation in other areas of public service innovation and innovation in local governance. About the literacy scientific, forms of innovation have been presented in some perspective, for example, the efficiency of the creep and shadow innovation: influence the ambidextrous it governance in the public sector are analysed [14], [15] government Intervention, financial support, and the efficiency of independent innovation enterprise, [16] the Merger of the degree of government support, financial support and innovation and its Impact In Economic Development. The public sector in the perspective of the bidding chain from the risk of transmission of innovation [17], and Stages and determinants of the development of e-government [18].…”
Section: Resultsmentioning
confidence: 99%
“…Government intervention is also one of the critical factors affecting innovation ( 18 ). Government intervention, such as government subsidy policies and preferential tax policies, is often used to promote China's pharmaceutical industry's innovation and development ( 19 , 20 ). The generic drug consistency evaluation policy is also a government intervention that can promote enterprise innovation.…”
Section: Research Hypothesismentioning
confidence: 99%